Hostile Intent Attribution and Aggressive Behavior in Children Revisited: A Meta‐Analysis. Issue 5 (5th June 2019) - Verhoef, Rogier E.J.; Alsem, Sophie C.; Verhulp, Esmée E.; De Castro, Bram O.
Abstract : To test specific hypotheses about the relation between hostile intent attribution (HIA) and children's aggressive behavior, a multilevel meta‐analysis was conducted on 111 studies with 219 effect sizes and 29.272 participants. A positive association between HIA and aggression was found, but effect sizes varied widely between studies. Results suggested that HIA is a general disposition guiding behavior across a broad variety of contexts, whereas the strength of the relation between HIA and aggression depends on the level of emotional engagement. The relation is stronger for more reliable HIA measures, but is not stronger for reactive aggression or co‐morbid attention‐deficit hyperactivity disorder than for aggression in general. The importance of understanding specific moderators of effect size for theory development is discussed.